TINDAK KRIMINAL DALAM EKONOMI SYARIAH: ANTARA ETIKA DAN HUKUM - Harahap, Taufik Hidayat (Jurnal Tahqiqa : Jurnal Pemikiran Hukum Islam, 2023)
The implementation of Sharia law in addressing economic crimes is a crucial step toward establishing a fair and sustainable economic system. This study aims to analyze various forms of criminal acts within the Sharia economic system, identify the factors influencing such violations, and assess the role of ethics and the effectiveness of Sharia law in preventing and addressing these offenses. Furthermore, it evaluates the relationship between Sharia legal norms and ethical principles in regulating economic misconduct. This research employs a qualitative approach, using data collection techniques such as in-depth interviews, participatory observation, and document analysis. Informants include Sharia law practitioners, Islamic economic experts, and entrepreneurs involved in the Islamic financial system. The data were analyzed to understand the practices and challenges of applying Sharia principles in preventing actions such as riba (usury), gharar (uncertainty), maysir (gambling), as well as corruption and fraud in economic transactions. The findings reveal that criminal acts in Sharia-based economies undermine the principles of justice and transparency. Sharia ethics plays a significant role as both a moral foundation and internal control system in preventing violations. Moreover, the effective implementation of Sharia law, supported by robust oversight and public education, can enhance the integrity and sustainability of the Islamic economic system.